2012
DOI: 10.1002/ange.201200587
|View full text |Cite
|
Sign up to set email alerts
|

A Biologically Inspired CuI/Topaquinone‐Like Co‐Catalytic System for the Highly Atom‐Economical Aerobic Oxidation of Primary Amines to Imines

Abstract: Gemeinsam: Katalytische Mengen an CuI und dem Topachinon‐ähnlichen Katalysator 1ox (siehe Schema) reichen aus, um die α‐C‐H‐Bindung von primären Aminen zu aktivieren und diese unter Umgebungsbedingungen in alkylierte Imine umzusetzen. Der atomökonomische Prozess toleriert verschiedene reaktive funktionelle Gruppen und ermöglicht selektive Kreuzkupplungen von zwei Aminen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Inspired by the enzymatic reactions of CuAOs and by recent breakthroughs in the aerobic oxidation of amines to imines, we further envisioned some modifications of our initial electrochemical procedure to enable us to isolate the homocoupled imines. We showed that a synergistic combination of copper salt and organocatalyst IMQ constituted an attractive approach to imines from primary amines, under very mild conditions (dioxygen in air as the oxidant together with ambient temperature and pressure) 19. The oxidation process started with atmospheric oxygen as shown in Scheme and continued in a cascade‐like manner through transfer of the oxidation potential through the copper salt to the organic o ‐iminoquinone mediator IMQ, which finally oxidized the amine substrate after formation of the Schiff base cyclic transition state shown in Scheme .…”
Section: Bioinspired Catalyzed Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the enzymatic reactions of CuAOs and by recent breakthroughs in the aerobic oxidation of amines to imines, we further envisioned some modifications of our initial electrochemical procedure to enable us to isolate the homocoupled imines. We showed that a synergistic combination of copper salt and organocatalyst IMQ constituted an attractive approach to imines from primary amines, under very mild conditions (dioxygen in air as the oxidant together with ambient temperature and pressure) 19. The oxidation process started with atmospheric oxygen as shown in Scheme and continued in a cascade‐like manner through transfer of the oxidation potential through the copper salt to the organic o ‐iminoquinone mediator IMQ, which finally oxidized the amine substrate after formation of the Schiff base cyclic transition state shown in Scheme .…”
Section: Bioinspired Catalyzed Oxidationmentioning
confidence: 99%
“…Interesting, this atom‐economical green process was also highly selective in the case of cross‐coupling of benzylic amines with aliphatic amines 19…”
Section: Bioinspired Catalyzed Oxidationmentioning
confidence: 99%
“…Since the beginning of this decade, imines synthesis by condensation of alcohols and amines has attracted considerable attentions because of the readily availability and relatively low cost of alcohols as well as the formation of clean by‐product. Numerous studies using homogeneous catalysts such as [Pd], [Cu], [Fe] and others have been reported in the literatures …”
Section: Introductionmentioning
confidence: 99%
“…A 0.5 m solution of dibenzylamine (1) and TPP (0.1 mol %) in dichloromethane (0.5 mL min À1 ) was mixed with oxygen gas (5 mL min À1 ) with the help of a T-mixer, prior to entering a continuous-flow photooxidation module (3.5 mL; Figure 1). Subsequent evaporation of the solvent revealed clean and quantitative conversion into N-benzylidene-1-phenylmethanamine (5). By-products, such as nitriles, nitrones, amides, or carbonyl compounds, that usually accompany the oxidative synthesis of imines were not observed.…”
mentioning
confidence: 99%
“…Direct oxidation is, however, generally limited to the use of benzylamines, expensive stoichiometric oxidants, [2] biocatalysts, [3] or complex metal catalysts. [4][5][6] Singlet oxygen is an attractive oxidant because it is inexpensive and a highly atom-economic reagent, [7,8] although it is difficult to generate and handle, resulting in its rare use for the formation of imines. [9] Che et al have reported the efficient oxidation of secondary benzylamines to the corresponding imines by singlet oxygen in a batch reactor in 8-14 h (Scheme 1 a), which was followed by stepwise Ugi-type reactions.…”
mentioning
confidence: 99%